A new Sigelgaita Heinrich (Lepidoptera, Pyralidae, Phycitinae) feeding on cacti in Brazil - Monteiro, Ricardo F. (2002)
Description and biological aspects of a new species of Sigelgaita Heinrich, 1939, the first known to occur east of the Andes, S. cerei Becker, are presented. S. cerei larvae were collected on "restinga" ecosystems feeding on Pilosocereus arrabidae (Lem.) Byles & Rowl. (Parque Nacional da Restinga de Jurubatiba-Macaé and Área de Proteção Ambiental de Barra de Marica, Rio de Janeiro) and rarely on Cereus obtusus Haw. (PNRJ). Life cycle and behavior of larvae are presented. Larvae are found singly on flower buds, on fruit or more frequently on stem of the plants. They build chambers in the cladodium where they complete their larval development, then droping to the ground in order to pupate. Trichogramma sp. was parasitizing 72% of eggs and a species of braconid was parasitizing half out of ten larvae collected from fruits of Cereus obtusus. S. cerei larvae develop a special role in the colonization and establishment of a diverse fauna associates with the hosts such as insects, spiders and yeasts. Ants, such as Camponotus crassus Mayr, 1862 and C. cingulatus Mayr, 1862 are among the insects which most frequently nest in the chambers abandoned by the larvae of this moth species.